Maxi's kitchen : easy go-to recipes to make again and again - Sharf, Maxine; Lemoine, Sanaë (Clarkson Potter, 2026)
Maxi's Kitchen presents 100 recipes by Maxine Sharf, organized around day-of-the-week themes to help home cooks choose meals that fit their schedule and preferences. Drawing on influences from Asian and Eastern European cuisines, the book focuses on dishes that balance simplicity, flavor, and comfort. Recipes range from quick weeknight options and one-pot meals to handheld dishes, more elaborate weekend projects, and brunch selections. The collection includes seafood, poultry, vegetarian dishes, small bites for entertaining, and a variety of baked goods. Sharf frames the cookbook as a guide to developing reliable, repeatable meals for everyday cooking, reflecting family traditions and accessible ingredients.